English Pronunciation Challenges Among Female Santri of English Intensive Program at Pesantren Annur Probolinggo - Wafa, Ali; Khoiriyah, Luluk (SPHOTA: Jurnal Linguistik dan Sastra, 2025)
This descriptive qualitative study investigates the female santris’ English segmental pronunciation errors, attributed to L1 phonological transfer from the dissimilar sound systems of English and Indonesian. Data from ten participants, collected via audio recordings, revealed systematic substitution and deletion processes affecting consonant and vowel phonemes. Consonantal errors included the substitution of /v/ with [f], /ð/ with [d] or [θ], /θ/ with [t] or [s], /tʃ/ with [c], /ʒ/ with [ʃ], /ʃ/ with [s], and /z/ with [s], alongside the deletion of /k/, /ɡ/, /t/, and /s/ within consonant clusters. Vowel inaccuracies involved alterations in tongue height and length, such as raising /ɪ/ to /i/, shortening /iː/ to /e/ or /ɛ/, and elongating /ʊ/ to /uː/, coupled with centralization and diphthongization processes. The findings indicate that these are not random errors but manifestations of a coherent, alternative phonological system. This system exhibits a preference for voiceless over voiced fricatives, stops over interdental fricatives, a marked simplification of complex consonant clusters, and a reorganized vowel space that avoids peripheral, tense, or distinct lax vowels. The study provides an empirical basis for targeted pedagogical interventions and contributes to establishing a detailed phonological error profile for Indonesian EFL learners in the Pesantren context.